A comparison of hydrogen abstraction reaction between allyl-type monomers with thioxanthone-based photoinitiators without amine synergists - Zhao, Xiaotian; Xu, Wen; Chen, Xi; Lin, Shibo; Li, Xuanhao; He, Lihui; Liao, Xu; Ye, Guodong (Frontiers in Chemistry, 2022)
The photodriven radical-mediated [3 + 2] cyclization reaction was found to yield polymers efficiently without being hindered by degradative chain transfer. The first reaction is a hydrogen abstraction process in which one hydrogen atom migrates from the α-methylene group of an allyl monomer to the triplet state (or fragments) of the photoinitiator, thus yielding primary allyl radicals as primary radicals and then begins chain propagation via a 3 + 2 cyclization reaction. Allyl ether monomers were found to be significantly higher than other allyl monomers even with the absence of amine-like synergists. In order to clarify the procedure of the hydrogen abstraction mechanism, we used four allyl-type monomers as hydrogen donors and three thioxanthone photoinitiators as hydrogen acceptors by the quantum chemistry method in terms of geometry and energy. The results were interpreted with transition-state theory and the interaction/deformation model. Then, the tunneling factors of hydrogen abstraction reactions were also investigated by Eckart’s correction. The results show allyl ether systems are more reactive than other allyl systems, and it would provide us with new insights into these hydrogen abstractions.